КОМПЛЕКСНИЙ АНАЛІЗ АДМІНІСТРАТИВНО-ПРАВОВИХ ФОРМ ПРОТИДІЇ КОРУПЦІЇ В ОРГАНАХ ПРОКУРАТУРИ В УКРАЇНІ ТА ЇХ КЛАСИФІКАЦІЯ - Подоляка, Сергій Анатолійович (SUPREMANCE OF LAW, 2018)
The article is devoted to the administrative-legal forms of counteraction to corruption in the organs of the prosecutor’s office in Ukraine. The theoretical concept of the content of the administrative-legal form is analyzed and on the basis of a comprehensive analysis of the researches of scientists, the own classification is given.